Assessment of acetic acid like fumigant of silverleaf whitefly Bemisia tabaci (Gennadious) in laboratory and field - Samaniego Gaxiola José Alfredo; Amaya Carrillo José Emmanuel; Puente Manríquez José Luis (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this work was to assess the capacity of acetic acid (AA) like fumigant against Bemisia tabaci (silverleaf whitef ly) which is a pest of national importance. In laboratory, the bug was fumigated with three doses-time regimes: (both media), low dose-long time and high dose-short time. In f ield, squash leaves of four varieties were fumigated with 8, 16 and 32 μg ml-1 of AA during of 20, 40 and 60 min; additionally, it was assessed damage in foils (phytotoxicity) af ter fumigation. In laboratory, fumigation time > 15 min and 8 μg ml-1 of AA killed100%ofwhitefly,whileitssurvivalwasreduced40% when fumigated eight hours with 2 μg ml-1 of AA; but control incubation (whitef ly without fumigation) during ≥ 16 h also reduced its survival; meanwhile, with 8 and 16 μg ml-1 of AA the pest survival was reduced since five minutes ( 20-80%). Infield,thewhiteflysurvived 40%inleavesoffourvarieties afterfumigatingwithAA(8-32μgml-1)during20min,butpest practically did not survive when increasing fumigation time to 60 min. The leaves showed severe damage (phytotoxicity) > to 50% except in dose of 8 μg ml-1 at 20 min with damage of 20%. Alternative to use of AA like fumigant are discussed.